The Divergence of the Influence of Ulama and Dayah in the Dynamics of Electoral Politics in East Aceh Regency - Rahma, Alya; Rizwan, M; Muzaffarsyah, Teuku; Faisal, Naidi; Sarifa, Sarifa (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
This research discusses the dlvergence of influence of ulama and dayah in electoral politics in East Aceh Regency. Use of electoral political theory (elections), using qualitative research methods. Findings from the results of research in the fileld regarding